DIGITALISASI MARKETING DALAM UPAYA UNTUK PENINGKATAN KUNJUNGAN PARIWISATA DOMESTIK DI KOTA SURAKARTA - Darmaningrum, Kurniawati; Wijiastuti, Sri; Sumarto, Laksono; Darsono, Darsono; Alhusin, Syahri (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
Indonesian tourism is currently still feeling the impact of the COVID-19 Pandemic that has occurred throughout the world. The COVID-19 pandemic has destroyed the tourism industry and the creative economy in Indonesia. The COVID-19 pandemic has caused tourism trends to change, shifting tourism trends in Indonesia have also impacted several businesses. In order to survive, of course, restaurant industry players must innovate in line with shifts in consumer behavior and habits. This study aims to see directly the impact caused by the COVID-19 Pandemic on three business categories, namely hotels, tourist destinations and restaurants, then create several strategies with the role of digital marketing to increase Indonesian tourism trends in the midst of a pandemic, or even until the pandemic is over. It is hoped that these strategies can revive the tourism sector and the creative economy in Indonesia, which were in a very bad slump when the pandemic hit. The objectives of this study are as follows: (1) to find out whether Social Media Content Marketing has an effect on brand equity, and (2) to find out whether brand equity has an effect on intention to visit